2020
DOI: 10.28982/josam.700839
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of salter osteotomy results in two different age groups in the treatment of developmental hip dislocation

Abstract: How to cite/Atıf için: Özkan S, Adanaş C. Comparison of salter osteotomy results in two different age groups in the treatment of developmental hip dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…However, regardless of which side is affected, treatment outcomes do not appear to be significantly influenced by the side involved. This finding is consistent with our own study as well as previous research [8,11,16]. In our study, we observed 24 cases of left-side involvement, 25 cases of right-side involvement, and 14 cases of bilateral involvement (27 hips in total).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…However, regardless of which side is affected, treatment outcomes do not appear to be significantly influenced by the side involved. This finding is consistent with our own study as well as previous research [8,11,16]. In our study, we observed 24 cases of left-side involvement, 25 cases of right-side involvement, and 14 cases of bilateral involvement (27 hips in total).…”
Section: Discussionsupporting
confidence: 94%
“…While others report no significant difference in AVN rate between the two groups; [3,11] Even, Akman did not report any AVN occurrence in CR plus SO [2]. In addition, Ozkan believed that AVN in SO relates more to surgical technique than age at the operation [16] but we did not compare our two groups on this subject.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations